PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN GAS NEGARA DIVISI CONTACT CENTER JAKARTA SELATAN - Putri Aprilia Anisyah; Sri Mulyani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of communication and work discipline on employee performance. The research method used is a quantitative method with an associative approach. The population in this study were all employees, with a sampling technique using the census method so that the number of samples used was 50 respondents. Data analysis methods used include validity tests, reliability tests, classical assumption tests, simple and multiple linear regressions, correlation coefficient tests, coefficients of determination, and hypothesis tests. Data collection was carried out through the distribution of questionnaires that had been tested for validity and reliability. The data analysis technique used multiple linear regression analysis with hypothesis testing through t-tests and F-tests. The results of the study showed that communication had a significant effect on employee performance with a correlation coefficient of 0.687 indicating a strong relationship, and a determination coefficient of 52.2%. Work discipline had a significant effect on employee performance with a correlation coefficient of 0.637 indicating a strong relationship, and a determination coefficient of 64.4%. Communication and work discipline simultaneously significantly influence employee performance, with a correlation coefficient of 0.637, indicating a strong relationship, and a determination coefficient of 64.4% Data collection was carried out through distributing questionnaires that had been tested for validity and reliability. The data analysis technique used multiple linear regression analysis with hypothesis testing through t-test and F-test. Based on these results, it can be concluded that communication and work discipline have an important role in improving employee performance.